Design and development of a portable electromagnetic coil accelerator for advanced defense applications - M. Priyadharsini; Sunil Kumar Gupta; Manoj Gupta (Institute of Advanced Engineering and Science, 2026)
In this work, a prototype of a six-stage coil gun was designed and developed to accelerate and propel a ferromagnetic projectile as an alternative technology to traditional firearms, which rely on explosive power for defense applications. The electromagnetic coils were arranged along the length of the barrel and were energized one at a time, sequentially, from one end of the barrel to the other to accelerate and propel the projectile forward. This paper presents the design, simulation, and optimization of the barrel and projectile, including details of the electromagnetic coils, triggering and switching circuits, and pulsed current sources. Simulations were conducted using COMSOL Multiphysics software with both single-coil and multiple-coil configurations. The prototype model incorporates a non-ferromagnetic barrel to minimize the retarding magnetic field and hysteresis, which could otherwise reduce the projectile’s velocity. The barrel is equipped with IR sensors to detect the projectile’s movement and activate or deactivate the corresponding electromagnetic coils, ensuring efficient forward propulsion. Utilizing a capacitor bank and rapid charging circuits, the developed prototype unit is capable of propelling the projectile at a velocity of 419 m/s measured at a 10-meter distance and could fire every 2 milliseconds successfully. The prototype unit developed is a handheld rifle using a polyvinyl chloride (PVC) barrel and uses a projectile with dimensions meeting the defense application.